Combination of AHP Method and VIKOR Method For Assesing Sunday School Teacher - Devi Valentino Waas; Suprapto Suprapto (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2020)
The performance appraisal of Sunday school teacher in the Imanuel Lurang congregation aims to measure and distinguish the quality of performance achieved by Sunday school teacher and decide various policies such as giving rewards to every Sunday school teacher with the best performance, and for Sunday school teacher who have poor performance scores will be given a guiding, approach, etc. The number of criteria in determining the quality of Sunday school teacher is not an easy thing to do by manual. Then it is essential that a computerized performance appraisal-based performance  app can speed up the process of progressing to be more effective and efficient.